PBLib -- A Library for Encoding Pseudo-Boolean Constraints into CNF - Philipp, Tobias; Steinke, Peter (Theory and Applications of Satisfiability Testing -- SAT 2015, 2015)
PBLib is an easy-to-use and efficient library, written in C++, for translating pseudo-Boolean (PB) constraints into CNF. We have implemented fifteen different encodings of PB constraints. Our aim is to use efficient encodings, in terms of formula size and whether unit propagation maintains generalized arc consistency. Moreover, PBLib normalizes PB constraints and automatically uses a suitable encoder for the translation. We also support incremental strengthening for optimization problems, where the tighter bound is realized with few additional clauses, as well as conditions for PB constraints.